Improving Innovative Behavior Through Entrepreneurship Education in Economic Education Students Lambung Mangkurat University - Rahayu, Suci; Rizky, Maulana; Ratumbuysang, Monry Fraick Nicky Gillian; Hasanah, Mahmudah (Universitas Muhammadiyah Surakarta, 2023)
The development of the times is increasingly rapid so it demands change in every individual, therefore innovative behavior is very important, especially for students so that they are able to face developments in the times and provide better changes for themselves and others. However, in reality the innovative behavior of students is still relatively low because they find it difficult to innovate. This research uses a quantitative approach with the type of expost facto research population amounted to 166 students using the probability sampling technique. The research instrument used observation and questionnaires with a likert scale, data analysis uses simple linear correlation. The test results of the t-test obtained a significance value of entrepreneurship education showing that the results of the t-test obtained a tcount value of 3,383 > ttable value of 1,980 meaning that the H1 hypothesis is accepted. Variable (X) entrepreneurship education on innovative variable (Y) has a positive influence, so hypothesis H0 is rejected. The calculated r value is 0.301. This means that the entrepreneurship education variable (X) has an effect on increasing innovative behavior (Y) by 30% which is categorized as relatively weak. The remaining 70% is influenced by other variables both internally and externally.